Multilingualism Protects Against Accelerated Aging in Cross-Sectional and Longitudinal Analyses of 27 European Countries - Garcia-Serrano, A (Springer, 2025)
Aging trajectories are influenced by modifiable risk factors, and prior evidence has hinted that multilingualism may have protective potential. However, reliance on suboptimal health markers, small samples, inadequate confounder control and a focus on clinical cohorts led to mixed findings and limited applicability to healthy populations. Here, we developed biobehavioral age gaps, quantifying delayed or accelerated aging in 86,149 participants across 27 European countries. National surveys provided individual-level positive (functional ability, education, cognition) and adverse (cardiometabolic conditions, female sex, sensory impairments) factors, while country-level multilingualism served as an aggregate exposure. Biobehavioral factors predicted age (R2 = 0.24, r = 0.49, root mean squared error = 8.61), with positive factors linked to delayed aging and adverse factors to accelerated aging. Multilingualism emerged as a protective factor in cross-sectional (odds ratio = 0.46) and longitudinal (relative risk = 0.70) analyses, whereas monolingualism increased risk of accelerated aging (odds ratio = 2.11; relative risk = 1.43). Effects persisted after adjusting for linguistic, physical, social and sociopolitical exposomes. These results underscore the protective role of multilingualism and its broad applicability for global health initiatives. © The Author(s), under exclusive licence to Springer Nature America, Inc. 2025.